How to predict cochlear length before cochlear implantation surgery. (December 2013) - Erixon, Elsa; Rask-Andersen, Helge
Abstract Conclusions: The basal turn diameter of the human cochlea predicts the outer wall length of the basal and two first turns relatively well but there was less correlation for the total cochlear length. The linear regression graph defines the length of the basal turn within an error of ± 1 mm and could be used clinically to distinguish small and large cochleae. Objective: The human cochlea varies in size. The preoperative assessment of cochlear length can be crucial for non-traumatic electrode insertion and hearing preservation. In this study, we estimated the external cochlear wall length by assessing the basal turn diameter. Methods: A total of 51 non-selected, human inner ear moulds were analysed. A line was drawn from the midpoint of the round window through the cochlear mid-portion to the opposite side (A) and correlated to the cochlear turn lengths. Linear regression analyses were carried out. Results: Mean diameter A was 9.3 mm. The mean basal turn length was 22.8 mm, the two first turns were 35.1 mm and the total length was 41.2 mm. Linear regression analyses indicated a coefficient of determination (R2) of 0.74 for diameter A and the basal turn length, R2 = 0.70 for the two-turn length and R² = 0.39 for the total length.